Answer:
Please see the explanation.
Step-by-step explanation:
As we know that the slope-intercept form of the equation is
[tex]y=mx+b[/tex]
Now, comparing the given equations with the slope-intercept form
a) y = 4/5x + 3
Here:
m = 4/5
Therefore, the slope of the equation y = 4/5x + 3 is: m = 4/5
b) y = -x + 1
Here:
m = -1
Therefore, the slope of the equation y = -x + 1 is: m = -1
b) y = 2x
Here:
m = 2
y-intercept = b = 0 ∵ y = mx+b here b is the y-intercept
Therefore, the slope of the equation y = 2x is:
m = 2 and
y-intercept = b = 0